Gendered differences in access and use of climate-smart agricultural technologies among men, women and youth bean farmers in Tanzania - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2025)
The study aimed to evaluate gender differences in access and use of climate-smart agricultural (CSA) technologies among bean farmers in Mbeya and Songwe districts, Tanzania. The scope focused on analyzing gender dynamics, constraints in CSA adoption, and implications on food security. It included quantitative data on socio-demographics, land ownership, bean production practices, and CSA use, exploring factors like education, land tenure, decision-making, and access to digital technology. The Principal Investigators sought to address how these factors impact gender-based differences in CSA adoption and how joint decision-making influences technology uptake​